Infantile (congenital) anaplastic intracranial solitary fibrous tumor/hemangiopericytoma—A case report with brief literature review - Mohapatra Debahuti; Lenka Anasuya; Deo R. Chandra; Das Prateek (Indian Journal of Pathology and Microbiology)
Solitary fibrous tumor/hemangiopericytoma (SFT/HPC) is a rare primary central nervous system (CNS) tumor, included in the World Health Organization (WHO) 2016 classification. Very few cases have been described in the literature so far, especially the infantile type. It is a mesenchymal tumor of the fibroblastic type, characterized by the fusion of NAB 2 and STAT 6 genes. A 10-month-old boy presented to our neurosurgery department with complaints of increasing head circumference since 1 month of age. The magnetic resonance imaging (MRI) showed a space-occupying lesion measuring 8.2 cm × 7 cm × 6.9 cm in the fronto-temporo-parietal region with a clinical diagnosis of glioma/atypical teratoid rhabdoid tumor (ATRT). The microscopy revealed a spindle cell tumor arranged in a patternless pattern with variable cellularity, increased mitosis, and areas of coagulative necrosis. The immunohistochemistry showed vimentin, CD 34, STAT6, CD99 positivity whereas Glial fibrillary acidic protein, Epithelial membrane antigen, and S-100 negativity. Hence, a diagnosis of anaplastic SFT/HPC (grade-III) was rendered. The patient improved after gross total resection (GTR). The primary intracranial congenital SFT/HPC are extremely rare, often a clinico-radiologically misdiagnosed entity. Thus, the immunohistochemistry/molecular study in addition to histology is mandatory for accurate diagnosis.